So Similar, yet so Different: The Case of the Ionic Liquids N-Trimethyl-N (2-methoxyethyl)ammonium Bis (trifluoromethanesulfonyl)imide and N,N-Diethyl-N-methyl-N(2-methoxyethyl)ammonium bis(trifluoromethanesulfonyl)imide - Palumbo, Oriele; Sarra, Angelo; Brubach, Jean-Blaise; Trequattrini, Francesco; Cimini, Adriano; Brutti, Sergio; Appetecchi, Giovanni Battista; Simonetti, Elisabetta; Maresca, Giovanna; Fantini, Sébastien; Lin, Rongying; Falgayrat, Anaïs; et al. (Frontiers in Physics, 2022)
Two ethoxy containing ionic liquids(ILs) sharing the same anion, N-trimethyl-N(2-methoxyethyl)ammonium bis(trifluoromethanesulfonyl)imide (N111(2O1)-TFSI) and N,N-diethyl-N-methyl-N(2-methoxyethyl)ammonium bis(trifluoromethanesulfonyl)imide (N122(2O1)-TFSI),and their mixtures are studied by means of differential scanning calorimetry and infrared spectroscopy combined with DFT calculations. The two ILs,slightly differing only for the length of two short chains, diverge significantly in the thermal properties: N111(2O1)-TFSI undergoes to a crystallization upon cooling, whereas N122(2O1)-TFSI is likely to become a glass. Experimental results indicate that in N111(2O1)-TFSI the occurrence of hydrogen bonding is energetically favored, and become particularly evident in the solid phase. The comparison with computational results indicates that it could be ascribed to the CH bonds involving the C atoms directly linked to the central N atom. In N122(2O1)-TFSI, DFT calculations suggest that hydrogen bonding could take place; however, IR measurements suggest that hydrogen bonding is not energetically favored. Moreover, in N122(2O1)-TFSI there is a larger conformational disorder that prevents from the alignment of cation and anion that contributes to the detection of clear hydrogen bonding infrared active bands. The mixtures rich in N111(2O1)-TFSI crystallize at lower temperatures than the pure ionic liquid. Progressively, the energy gain due to the instauration of hydrogen bonding decreases as the concentration of N122(2O1)-TFSI increases.